1998
DOI: 10.1002/(sici)1097-4628(19980328)67:13<2125::aid-app2>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of X-rays on poly(vinylidene fluoride) in X-ray photoelectron spectroscopy

Abstract: ABSTRACT:The polymer poly(vinylidene fluoride) (PVDF) was irradiated with X-rays produced by a nonmonochromatic (MgKa) source and the structural and electronic PVDF surface modifications were studied by X-ray photoelectron spectroscopy (XPS). Changes in the shape and intensity of the C 1s and F 1s lines show that a PVDF degradation consisting of the polymer defluorination takes place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 3 publications
1
20
1
Order By: Relevance
“…One extra peak at 287.6 eV is due to the impurities in the polymer present prior to loading ( Figure 10a). 47 Figure 10b shows the XPS of PVDF/GO composites. The C1s core spectrum clearly shows the aromatic CC binding energy (284 eV), aliphatic C−C binding energy (285 eV), carbonyl carbon CO at 287.1 eV, and the binding energy of C-F 2 species at 289.08 eV.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…One extra peak at 287.6 eV is due to the impurities in the polymer present prior to loading ( Figure 10a). 47 Figure 10b shows the XPS of PVDF/GO composites. The C1s core spectrum clearly shows the aromatic CC binding energy (284 eV), aliphatic C−C binding energy (285 eV), carbonyl carbon CO at 287.1 eV, and the binding energy of C-F 2 species at 289.08 eV.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This capability promises a significant technological potential. Although the irradiation effects on PVDF due to monoenergetic X rays, UV, and ion beam have been reported previously [7]- [12], this paper presents, for the first time, these effects being exploited in synchrotron X ray (allows tuning of energy over a wide range) based microfabrication, similar, in principle, to a past work on poly(tetrafluoroethylene) or Teflon ® [13]. However, unlike Teflon ® , PVDF is not suitable to be used as an alternate X-ray resist in place of PMMA (for reasons which become evident later), but it is useful only in thin film (a few monolayers to a few micrometers) applications.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the irradiation effects on PVDF, induced by a variety of energetic sources, such as X rays (MgK -1253.6 eV) [7], UV (2.25-3.96 eV) [8], excimer lasers (ArF-6.4 eV and KrF-5 eV) [9] and ion beams (1 keV-100 MeV) [10]- [12], reported that PVDF undergoes dehydrofluorination upon irradiation. The formation of carbon double bond was observed following dehydrofluorination along with a possibility of crosslinking between monomer chains.…”
Section: Introductionmentioning
confidence: 99%
“…Poly (vinylidene £uoride) (PVDF), a polymer of large technological applicability, has been found to be surface-de£uorinated after prolonged exposure to X-rays, but not noticeably under the usual conditions of XPS analysis. 455 …”
Section: Polymers and Polymerizationmentioning
confidence: 99%